Sequential Testing in Product Development - Thomke, Stefan; Bell, David E. (Management Science, 2001)
A fundamental problem in managing product development is the optimal timing, frequency, and fidelity of sequential testing activities that are carried out to evaluate novel product concepts and designs. In this paper, we develop a mathematical model that treats testing as an activity that generates information about technical and customer-need related problems. An analysis of the model results in several important findings. First, optimal testing strategies need to balance the tension between several variables, including the increasing cost of redesign, the cost of a test as function of fidelity, and the correlation between sequential tests. Second, a simple form of our model results in an EOQ-like result: The optimal number of tests (called the Economic Testing Frequency or ETF) is the square root of the ratio of avoidable cost and the cost of a test. Third, the relationship between sequential tests can have an impact on optimal testing strategies. If sequential tests are increasing refinements of one another, managers should invest their budgets in a few high-fidelity tests, whereas if the tests identify problems independently of one another it may be more effective if developers carry out a higher number of lower-fidelity tests. Using examples, the implications for managerial practice are discussed and suggestions for further research undertakings are provided.